Proposed Pharmacological Treatments for COVID-19: Previously Confirmed Drugs - Fatemeh Bahoosh Feyzabadi; Alireza Nikjoo; Mohammad Reza Lagzian; Hessamedin Babaei; Melika Nasehi (Mazandaran University of Medical Sciences, 2022)
Background: The outbreak of severe acute respiratory syndrome coronavirus-2, also called 'coronavirus disease 2019' (COVID-19), first appeared in December 2019 in Wuhan, China. COVID-19 is caused by an enveloped single-stranded RNA virus, which has affected more than 14 million people around the world and caused a high rate of mortality. It is notable that discovering new drugs and vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is time-consuming. Therefore, reviewing drugs, which have been previously designed for other purposes can be helpful and effective. Objectives: Studying the effects of previously approved drugs is important; thus, in this article, we reviewed studies on proposed drugs against COVID-19. Methods: The articles and information were collected from Google Scholar, ScienceDirect, and Scopus databases. We did our research based on keywords, like "therapeutics", "pharmacology", "Coronavirus", "COVID-19", "SARS", and "MERS-CoV". We also applied some filters, such as title/abstract, and ignored factors that could lead to bias and selective selection. Results: There is currently no cure for coronavirus, and most treatments have been effective to relieve symptoms. The treatment methods and drugs addressed in this article are chosen either from previous drugs against MERS and SARS, drugs that disrupt the life cycle of the coronavirus, or drugs that have been reviewed in retrospective studies and clinical trials. Conclusion: Prevention and treatment of COVID-19 remain a challenge, in particular for coronavirus and the treatments based on boosting the immune system and preventing virus replication. Epidemiological studies have shown that COVID-19 and SARS-COV transmission are relatively similar. This can help to select the appropriate drug. Thus, anti-inflammatory and antiviral drugs, such as remdesivir are used. Antimalarial drugs, such as hydroxychloroquine (HCQ) and chloroquine (CQ) along with estrogen receptor inhibitors, such as toremifene citrate, which has shown effective results against SARS and MERS, can influence the treatment process. However, more clinical trials are needed to determine the efficacy and side effects of drugs.